Geopolitical Attitude in Urban Tourism Competition Using Tourism Attraction Index (Case Study: Tehran City) - arash ghorbani sepehr; Afshin Mottaghi; Zahra Ansari; Morad Delalat (تحقیقات کاربردی علوم جغرافیایی)
The city of Tehran, based on the 1404 document and the comprehensive plan approved in 2007, is a global, sustainable and coherent city with a structure suitable for leisure and leisure as well as a well-informed urban community with appropriate infrastructure. In order to achieve such a definition, the mentioned documents include promotion of the role and position of Tehran in transnational, national and regional levels, economic development and prosperity of the city of Tehran, improvement of communication networks, environmental protection, active restitution and conservation of natural heritage , Historical and cultural city of Tehran, and the development of green spaces, public spaces, recreation and tourism are predicted. One of the most important areas that can be used to operate the above strategies is the urban tourism area in the Tehran metropolis. Therefore, the issue of competition in urban tourism is an important factor in the progress of all cities of the country in competing with each other and, as a result of the prosperity and prosperity of the country at the national level, and then in competition with neighboring countries and globally, will make rapid progress and attract much capital to the country. The main objective of the research is to study the political geography of competition in urban tourism. Seeking to reach the goal of this article, the statistical population of the study is the provinces of Iran, which Tehran province has selected as a case study. In line with the aim of the study, data related to tourist attractions were collected using the Statistical Yearbook of the provinces (Tourism Organization, Cultural Heritage, Governor's Office in 1395) and then TOPSIS and ARC map software were used to map the provinces.